2010
DOI: 10.1038/jhh.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Achieving blood pressure goal: initial therapy with valsartan/hydrochlorothiazide combination compared with monotherapy

Abstract: The benefits of valsartan (Val)/hydrochlorothiazide (HCTZ) combination as initial treatment for hypertension were evaluated in a post hoc analysis of an 8-week, doubleblind, placebo-controlled, parallel-group trial. The highest dose of Val/HCTZ combination (320/25 mg), component monotherapies (Val 320 mg, HCTZ 25 mg) and placebo were selected for this analysis (N ¼ 675, 52.1% men, 68.6% Caucasians, mean age 52.9 years, baseline blood pressure (BP) 150.6/99.1 mm Hg). As soon as 2 weeks after initiation of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…These findings are consistent with the studies done by Salanitro et al, Zachariah et al and Weinberger et al which have documented 40%-70% of patients having uncontrolled blood pressure. [40][41][42] A study by Elzubier et al using pill counting method documented, 61.6% had controlled blood pressure while 38.4 had uncontrolled and found that 92% compliant patients had controlled blood pressure in comparison to noncompliant patients. Major reason for noncompliance was "not able to afford/buy medicines".…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the studies done by Salanitro et al, Zachariah et al and Weinberger et al which have documented 40%-70% of patients having uncontrolled blood pressure. [40][41][42] A study by Elzubier et al using pill counting method documented, 61.6% had controlled blood pressure while 38.4 had uncontrolled and found that 92% compliant patients had controlled blood pressure in comparison to noncompliant patients. Major reason for noncompliance was "not able to afford/buy medicines".…”
Section: Discussionmentioning
confidence: 99%
“…Valsartan, a well known ARB, has proven efficacy and safety when used either as monotherapy or in combination to treat hypertension in adults [18][19][20]. A doseresponse study in children aged 6-16 years demonstrated that valsartan was efficacious and well tolerated in doses ranging from 10 to 160 mg [21].…”
Section: Introductionmentioning
confidence: 98%
“…Valsartan is an ARB that has proven efficacy and safety when used either as monotherapy or in combination to treat hypertension in adults [14][15][16][17]. This ARB has also demonstrated efficacy and safety in doses ranging from 10 to 160 mg in children aged 6-16 years [18].…”
Section: Introductionmentioning
confidence: 98%